PERSEPSI SISWA TERHADAP EFEKTIVITAS APLIKASI PRESENSI DIGITAL “SREGEP” DALAM MENINGKATKAN KEDISIPLINAN SISWA KELAS VIIID DI MTS NEGERI 1 YOGYAKARTA - Ikha Ayu Sulistyarini; Jumintono Jumintono; Saryanto Saryanto (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
Student attendance is a fundamental indicator of learning success, influenced by both internal and external factors. In line with technological advancement, MTs Negeri 1 Yogyakarta developed a barcode-based digital attendance application called "Sregep". However, a systematic evaluation of student perceptions in the Olympiad class (VIII D), which is characterized by dense schedules, high mobility, and intensive technology use, had never been conducted. This study aimed to describe grade VIII D students' perceptions of the effectiveness of the "Sregep" application in improving discipline and learning motivation, its impact on academic achievement, and to identify the technical challenges encountered. This study employed a quantitative descriptive approach with a survey method. The entire population of 30 grade VIII D students was selected using a total sampling technique. Data were collected through closed-ended and open-ended questionnaires distributed via Google Forms and analyzed using descriptive statistics. Results showed that ease of use was rated very good with a mean of 5.00, discipline improvement was in the good category with a mean of 4.10, learning motivation increased with a mean of 3.97, and the impact on academic achievement was moderately positive with a mean of 3.73. The main obstacles were difficulty scanning student cards (40%) and queues due to limited scanning points (13%). A comparison of discipline levels before and after application use showed an increase in the "Very Disciplined" category from 20% to 37%. The "Sregep" application proved effective in promoting student attendance discipline and requires further development through additional scanning points and alternative verification features. ABSTRAK Kehadiran siswa merupakan indikator fundamental keberhasilan pembelajaran yang dipengaruhi oleh faktor internal maupun eksternal. Seiring perkembangan teknologi, MTs Negeri 1 Yogyakarta mengembangkan aplikasi presensi digital berbasis scan barcode bernama "Sregep". Namun, evaluasi sistematis terhadap persepsi siswa kelas olimpiade (VIII D) yang memiliki karakteristik jadwal padat, mobilitas tinggi, dan penggunaan teknologi intensif belum pernah dilakukan. Penelitian ini bertujuan mendeskripsikan persepsi siswa kelas VIII D terhadap efektivitas aplikasi "Sregep" dalam meningkatkan kedisiplinan, motivasi belajar, dan dampaknya terhadap prestasi, sekaligus mengidentifikasi kendala teknis yang dihadapi. Penelitian menggunakan pendekatan deskriptif kuantitatif dengan metode survei. Populasi seluruh siswa kelas VIII D berjumlah 30 orang diambil menggunakan teknik total sampling. Instrumen berupa kuesioner tertutup dan terbuka yang disebarkan melalui Google Form dan dianalisis menggunakan statistik deskriptif. Hasil penelitian menunjukkan bahwa kemudahan penggunaan aplikasi berada pada kategori sangat baik dengan rerata 5,00, peningkatan kedisiplinan pada kategori baik dengan rerata 4,10, motivasi belajar meningkat dengan rerata 3,97, dan dampak pada prestasi cukup positif dengan rerata 3,73. Kendala utama yang dihadapi adalah kartu pelajar sulit terbaca (40%) dan antrean akibat keterbatasan titik scan (13%). Perbandingan kedisiplinan sebelum dan sesudah penggunaan aplikasi menunjukkan peningkatan kategori "Sangat Disiplin" dari 20% menjadi 37%. Aplikasi "Sregep" terbukti efektif mendorong peningkatan kedisiplinan kehadiran siswa dan perlu dikembangkan lebih lanjut melalui penambahan titik scan serta fitur verifikasi alternatif.